Creating original Ukrainian dance in Canada – an autobiographical reflection of a 40-Year creative journey with the Ukrainian Shumka Dancers of Canada - Gordey, Gordon (My University, 2014)
Gordon Gordey autobiographical reflection of a 40-year creative journey with The Ukrainian Shumka Dancers of Canada recounts his experiences creating his original artistic works with The Ukrainian Shumka Dancers of Canada. By documenting his dance concepts and librettos Gordey reveals his challenge to create original work that is an outward expression of life through dance by engaging a creative team’s physical, emotional, intellectual, and spiritual selves. He reveals his desire to contribute original work to the canon of Ukrainian dance that is spiritually connected to generations of continuous cultural practice and resonates with 20th and 21st century audiences in Canada, Ukraine, Russia, and China. He speaks to evolving dance stories that embed themselves in viewer’s minds and become cultural touchstones worth sharing. Dance concepts and librettos for: Shumka’s Cinderella, Pathways to Hopak, Girl in the Red Dress TANGO, Vechornytsi (the multi-works in Life is a Cabaret), Eve of Kupalo - a Midsummer’s Night Mystery Masque and Voices of the Silenced are enhanced with photographs and video excerpts of the dances in performance.
Keywords: Ukrainian dance; folk dance; Canadian dance; Ukrainian Shumka Dancers; folk ballet; choreography; danceworks; folktales; Dave Ganert